Adopting vibration to alleviate the solute buildup and membrane fouling in a forward osmosis system. (10th November 2021) - Zhang, Jing-Xiao; Tian, Tian; Du, Wen-Jie; Guan, Yan-Fang; Wang, Yun-Jie; Li, Yu-Sheng; Yu, Han-Qing
Abstract: Forward osmosis (FO) is limited by solute buildup and membrane fouling. Although current solutions (e.g., influent pretreatment and membrane modification) have partially compensated these drawbacks, they are still enslaved to the uncertainties and costs from the complex operational requirements and large use of chemicals. Therefore, developing simply-operated and chemical-free methods is highly required. In this work, a lab-scale vibrating FO device was constructed and its water permeability and anti-fouling capacity were evaluated. The results of flux tests show that the vibration could effectively enhance the water flux and mitigate solute buildup, mainly resulted from changing the flow field on the membrane surface through the computational fluid dynamic simulations. In addition, the vibrating FO was also proven to be effective in controlling the fouling caused by model organic foulants like bovine serum albumin, humic acid, alginate, and biofouling by different ways. The results of anti-fouling tests and fouling characteristics show that the organic fouling was alleviated by disintegrating the fouling layer and reducing the solute buildup, while the biofouling was mitigated through retarding the early microbial attachment and growth. This work provides a feasibility of applying vibration as an effective strategy to control solute buildup and fouling in FO systems. Graphical abstract: Image 1 Highlights: Vibration restrains the solute buildup and improves water flux of TFC-FO membrane. Vibration FO system exhibits anti-fouling ability for organic fouling and biofouling. Organic fouling is mitigated by destructing fouling layer and reducing solute buildup. Biofouling is mitigated through retarding the early microbial attachment.